A critical review of the past studies on the application of UNIPUS in China - Fang He; Supyan Hussin; Azlina Abdul Aziz (Journal of Education and Learning (EduLearn), 2026)
UNIPUS, a widely adopted learning management system (LMS) in tertiary universities in China, plays a prominent role in blended English as a foreign language (EFL) learning. However, there is a lack of critical review on how the application of UNIPUS is theoretically framed and how it contributes to the EFL teaching and learning. This study aims to critically review the existing research on the application of the LMS UNIPUS in blended EFL education. Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, it systematically analyzed 29 studies retrieved from major databases, including Web of Science, Scopus, Google Scholar, China National Knowledge Infrastructure (CNKI), WanFang Data, and VIP Database. Through content analysis of the selected articles, this study focused on three key aspects: spatial and temporal dimensions, theories that framed the application of UNIPUS, and the research methodologies employed. The findings offer a bird’s view on the application of UNIPUS in EFL context. The study concludes with recommendations for future research to enhance the effective use of UNIPUS in blended EFL education.